ANALISIS LAPORAN KEUANGAN ARUS KAS SEBAGAI ALAT PENGUKUR INVESTASI PADA PT. MATAHARI DEPARTMENT STORE TBK - Muhammad Maulana3, Andry Kurniawan1, Eka Yudhyani2, (EKONOMIA, 2021)
The purpose of this study was to identify and analyze cash flow statements at PT. Matahari Department Store Tbk. from 2016 to 2019 experiencing a deficit or not and to find out the cash flow statement analysis at PT. Matahari Department Store Tbk. In 2016 to 2019 choose to invest in the company or not.The theoretical basis used in this research is management accounting which includes investment, investment decisions, cash flow reports and cash flow statement analysis. This type of research is a quantitative study with the data used is secondary data which is quantitative data obtained from the annual financial statements of PT. Matahari Department Store Tbk. The analytical tool used is a cash flow ratio analysis which includes: 1) the ratio of operating cash flows to current liabilities; 2) Operating Cash Flow Ratio to Interest; 3) Operational Cash Flow Ratio to Capital Expenditure; 4) Operational Cash Flow Ratio to Total Debt; and 5) Operational Cash Flow Ratio to Net Profit.The results of the discussion of this study are that the overall hypothesis proposed by the researcher is accepted because the results of the cash flow analysis show negative cash flow and the ratio value of PT. Matahari Department Store Tbk. which is not good, so that the company is still not eligible to get investment from investors.